Pola Asuh Orangtua Generasi Milenial terhadap Perkembangan Sosial Emosional Anak Usia Dini - Siti Khumaeroh; RR. Deni Widjayatri (Universitas Islam Tribakti Lirboyo Kediri, 2022)
This study explains how the emotional social behavior of children with parents who come from the milllenial generation where the millennial generation is born along with the start of technology. Parents in the millennial generationmust have knowledge and awareness about child development, especially in social-emotional development in times with rapid technology in order to be able to manage time or sort out positive things for children and parents know the impact if the parenting patterns applied are not appropriate. The subject of this study are parents and early childhood. Data collection was carried out using the literature study method by conducting studies from various scientific sources related to the research carried out, by analyzing the behavior and actions taken by parents towards their children and their impact on social emotional development. This study aims to find out the parenting patterns applied by parents of the millennial generation and their impact on the emotional social behavior of early childhood. Based on this literature study study, parents in the millennial generation must have awareness about the application of parenting including behaviour and action in the era of technology that has a major influence on the social emotional development of early childhood. This means that parents must be wise and kind in implementing their child's parenting.